Eyes of Fear: Leveraging Emotion Recognition for Virtual Reality Experience - Marinho, Isabela; Padilha, Renatto; Vitorino, Gislayne; Batista, Marcelo; Oliveira, Yasmim; Almeida, João Vitor; Costa, Willams; Araújo, Cristiano; Teichrieb, Veronica (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Given the growing interest in immersive gaming experiences, particularly within the horror genre, there is a rising demand for sophisticated and engaging game mechanics. However, creating a truly immersive horror experience requires a balance between fear-inducing elements and player engagement. In this work, we present Eyes of Fear, a horror game that explores human emotions and eye movement as interactive mechanisms in virtual reality. We used a state-of-the-art emotion recognition algorithm and Tobii Eye Tracker for our game prototype and evaluated their effectiveness through player feedback. Our findings show that emotion-sensitive enemy behavior elevates unpredictability and intense emotions while amusing players.